Estudio de factibilidad para la exportación de tejido artesanales de la comunidad Tsáchila hacia Alemania - Giler Bone, Estrella Mabel (2011)
The present Plan of feasibility of Export takes the export as an aim for the commercialization of handcrafted fabrics of the community Tsáchila for the markets of Germany. The plan feasibility provides an evaluation of the attraction of the sector of textile community crafts. The handcrafted sector of indigenous fabrics, from some time behind, one comes being of benefit with the agreements of the market of Germany by means of the General System of Tariff Preferences. The current trend of the international market is to the consumption of utilitarian crafts, for what the lines of product chosen for the present plan of export he understands: skirts, scarves, purses, portfolios and Accessories. Of the diverse crafts of decoration that produces Ecuador, the present study analyzes the German market for a specific category of textile crafts: skirts, blouses, panoguino, it rocks, purses of the community Tsáchila of the province of Santo Domingo of the Coloured ones. In the present investigation of feasibility, the logistic steps are detailed for the accomplishment of the export to the German market, likewise the strengths, opportunities are detailed, threats and weaknesses that one faces in any project of investment finishing our investigation in the development of the cash flow, having a perspective from 1 to 5 years of feasibility.